Quasi-Nothing, yet something: Understanding Nietzsche's biological notion of subject through Baruch Spinoza and Thomas Pradeu (Balthazar, 2023)
The opinion of Friedrich Nietzsche on the theme of subjectivity is well-known: the subject does not exist; it is merely the theoretical hypostatization of a phantom. In Nietzsche's works the subject appears to be something transitory and destined to disappear, as nothing more than a ripple in the vast ocean of the will to power. However, can the question truly be considered closed? In this paper, I will demonstrate the opposite, showing how it is possible to still provide some Nietzschean positive notion of the subject. Initially, a brief excursus will be necessary to outline the main scientific sources employed by Nietzsche in developing his concept of the individual. Secondly, I will focus on certain aspects of the works of two authors who are very different from each other, although akin in spirit, with the aim of making it more evident how one can speak of the individual in Nietzsche's philosophy. These two authors are Baruch Spinoza and Thomas Pradeu. Through Deleuze's famous lectures on Spinoza, I will show how it is possible to postulate an understanding of individuality that is not entirely fixed and monolithic, adopting the concepts of Bauplan, ratio, and strategy. I deemed it important to also dedicate attention to Pradeu for at least two reasons. Firstly, because the theme of Immunology, to which he devoted his most important works, is strictly related to the issues of defining the borders of the individual: a good immune system can work only if there is an individual to protect, opposed to every other external body, understood as enemies. Secondly, because Pradeu too argues that an individual - while maintaining its unity - is never something rigid. Finally, I highlight why it is crucial to speak of the Nietzschean individual. The theme of the individual is pivotal in Nietzsche’s Moral Philosophy: the only possible way to think of an Ethics “beyond Good and Evil” is the path of understanding Ethics as Ethology - to use a Deleuzian term. An Ethics of this kind – focusing on bodily joy to the point that it can even be defined as medical in its nature – can only find its keystone precisely in the question upon what is a body – which in turn is dependent on the question upon what is an individual.
Keywords: Nietzsche; Spinoza; individuality; philosophy of biology; moral philosophy